Analysis and Classification of Squares within the Urban Frame of the City of Manaus - Amazonas - Paula Boaventura Corrêa Cavalcanti, Brenna; Maria Boaventura Corrêa Arruda, Yêda; Rogério Bastos Cavalcanti, Lúcio (Journal of Interdisciplinary Lifestyle Studies, 2022)
The squares are a strategic place to invest in the afforestation of a city, as they are less confronted with buildings and energy transmission networks, but mainly because they are a place of social interaction and recreational activities. Therefore, knowing its spatial configuration and its access by the surrounding population will allow for better planning by public agencies regarding the implementation, maintenance and floristic composition of the squares. Therefore, the main objective of the study was to analyze the design of squares within the urban frame of the city of Manaus - Amazonas, Brazil. Twenty-four squares were studied through mapping and visual analysis of satellite images from the Google Earth software. Subsequently, the classification according to the type of square proposed by De Angelis and De Angelis Neto (2000) was used. A total inventory of tree specimens (DBH > 10 cm) was carried out, being registered 513 trees distributed in 13 families, 31 genus and 35 species. Of the cataloged species, 51.4% (n=18 species) are classified as exotic to Brazil and 48.6% (n=17 species) are native to Brazil. However, of the 17 native species, 15 are native to the Amazon. The insertion of Manauaras squares in its urban frame is not standardized, so it was necessary to create four subtypes of squares to meet the specific reality of Manaus. It was found that the dominant type of classification of square, regarding insertion in the urban frame, is type 3 (54.2%), followed by type 2 (29.2%) and type 4 (16.6%).